The Fire Signals of Lachish : Studies in the Archaeology and History of Israel in the Late Bronze Age, Iron Age, and Persian Period in Honor of David Ussishkin - Finkelstein, Israel; Na ơaman, Nadav (Eisenbrauns, 2011)
In this volume honoring Tel Aviv University archaeologist David Ussishkin, colleagues and students representing some of the major names in the field today present 25 essays on a variety of topics of interest to the honoree. The contributions cover a range of periods from the Late Bronze Age through the Persian period and disparate subjects such as Judahite bullae, destruction levels at Megiddo, a diversity of results from various tells in Israel (and one in Jordan), Egyptian influence on Canaan, the city of Jerusalem and its temple, and much on the archaeology of the Shephelah, an area of particular interest to the honoree--who is best known for his excavations at Tell ed-Duweir, the site of biblical Lachish. The volume takes its title from a reference in one of the Lachish ostraca.From 1966 until his retirement in 2004, David Ussishkin taught in the Department of Archaeology and Ancient Near Eastern Studies at Tel Aviv University. Between 1975 and 1978, he served as Chair of the Department, and between 1980 and 1984 as the Director of the Institute of Archaeology. In 1996, he was nominated incumbent of the Austria Chair in Archaeology of the Land of Israel in the Biblical Period. He served as the editor of Tel Aviv: The Journal of Archaeology of Tel Aviv University for 30 years.